2017
DOI: 10.1016/j.heliyon.2017.e00345
|View full text |Cite
|
Sign up to set email alerts
|

Acanthoecid choanoflagellates from the Atlantic Arctic Region − a baseline study

Abstract: The examination and statistical analysis of loricate choanoflagellate material collected from Greenland waters during the period 1988–1998 represents a de facto baseline study of heterotrophic nanoflagellates from the Atlantic Arctic Region. The geographic sites sampled are Disko Bay (West Greenland) and the high-arctic North-East Water (NEW) and North Water (NOW) polynya. The analyses encompass close to 50 taxa. Some of these are described as new species, i.e. Acanthocorbis glacialis, A. reticulata and Diapha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Notably, according to Nitsche (), the polar regions in both hemispheres were clustered together, as was the case in our data. A recent global analysis of loricate choanoflagellate morphospecies distribution (Thomsen & Østergaard, ) also revealed a fairly distinct separation among ‘cold’ and ‘warm’ waters from both hemispheres, and the ‘cold’ group included both Arctic and Antarctic communities. Several authors have compared the temperature tolerances of various flagellate isolates and found strong evidence for local temperature conditions as an important driver of the geographical distribution (Boenigk et al, ; Rodríguez‐Martínez et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Notably, according to Nitsche (), the polar regions in both hemispheres were clustered together, as was the case in our data. A recent global analysis of loricate choanoflagellate morphospecies distribution (Thomsen & Østergaard, ) also revealed a fairly distinct separation among ‘cold’ and ‘warm’ waters from both hemispheres, and the ‘cold’ group included both Arctic and Antarctic communities. Several authors have compared the temperature tolerances of various flagellate isolates and found strong evidence for local temperature conditions as an important driver of the geographical distribution (Boenigk et al, ; Rodríguez‐Martínez et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Based on material from Osaka Bay, Japan, Hara and Takahashi (1987a) presented data on morphology and seasonal occurrence patterns of B. spinifera and B. minor that largely substantiated the findings presented by Manton et al (1980). Thomsen and Larsen (1992) and Thomsen and Østergaard (2017) address Bicosta morphological variability and distributional patterns within Antarctic and Arctic realms, respectively.…”
Section: R R R Results Esults Esults Esults and And And And D D D Dismentioning
confidence: 99%
“…Calliacantha natans is otherwise widely distributed throughout the coldwater regions of the world's oceans, see e.g. Thomsen et al (1990) and Thomsen and Østergaard (2017).…”
Section: Natans (Fig 9p)mentioning
confidence: 99%
See 2 more Smart Citations